A complication of coronary angiography: rare presentation of pseudo aneurysm with groin swelling - Khan, Naseem S.; Thomas, James; Shaikh, Tanveer Parvez; Lal, Vikash; Deolekar, Sandesh; Mahapatra, Bibekananda (International Journal of Research in Medical Sciences, 2017)
Pseudo aneurysm (PSA) is one of the most common vascular complications of cardiac and peripheral angiographic procedures. In this case we had an old man presenting with a large hard immobile pseudo pulsatile, severe painful swelling in groin region post21 days of coronary angiography.